(untitled) (Dibyajyoti Journal, 2025)
This study investigates the comparative effectiveness of cybersecurity awareness management practices among Grade 7–12 students in Sunwal municipality’s public and private schools, using SPSS to model influencing factors. As Nepal undergoes rapid digital transformation, driven by increased internet access, mobile device usage, and post COVID-19 digital learning, students are increasingly exposed to cyber threats such as phishing, cyberbullying, and identity theft. Despite national initiatives like the Digital Nepal Framework and Cyber Security Policy 2080, implementation at the school level remains inconsistent, especially in rural and public institutions. SPSS was employed to analyze the relationships between latent variables and to test hypotheses such as “Digital literacy positively influences cybersecurity awareness” and “Institutional support enhances cybersecurity behavior.” Descriptive statistics were used to compare public and private school practices. While the findings are pending, preliminary hypotheses suggest that private schools, particularly in urban areas, demonstrate higher cybersecurity awareness due to better infrastructure, gamified learning tools (e.g., Kahoot, Scratch), and teacher training. Public and rural schools face challenges such as limited internet access, lack of trained staff, and absence of standardized cybersecurity curricula.